2018
DOI: 10.1111/bjd.16366
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of secukinumab vs. ustekinumab for treatment of psoriasis on quality of life, work productivity and activity impairment: a structural equation modelling analysis

Abstract: The results underscore the important role of both PASI response and reduction in symptoms on improvements in health-related quality of life and work and daily activity in favour of secukinumab vs. ustekinumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Using the two main disease symptoms, PASI and itch, as the mediators, the mediation analysis showed that both early improvement in itch and PASI scores played a role in improving patient's quality-of-life at Weeks 4 and 12, with improvement in itch playing a more dominant role than PASI score. Similar results were shown previously in patients with moderate-to-severe psoriasis (6, 10, 11) using a single mediator (6) or more complex models with several factors including PASI, itch, pain, scaling (11). There were limitations in this mediation analysis.…”
Section: Discussionsupporting
confidence: 81%
“…Using the two main disease symptoms, PASI and itch, as the mediators, the mediation analysis showed that both early improvement in itch and PASI scores played a role in improving patient's quality-of-life at Weeks 4 and 12, with improvement in itch playing a more dominant role than PASI score. Similar results were shown previously in patients with moderate-to-severe psoriasis (6, 10, 11) using a single mediator (6) or more complex models with several factors including PASI, itch, pain, scaling (11). There were limitations in this mediation analysis.…”
Section: Discussionsupporting
confidence: 81%
“…There are two arguments underpinning the feasibility of this alternative scoring formula. Firstly, in a recent study, Stull et al . performed structural equation modelling and showed that in patients with psoriasis, the symptoms of psoriasis first affect the symptoms and feelings subscale, which then has an impact on the remaining five subscales.…”
Section: Methodsmentioning
confidence: 99%
“…Associations between improvements in PASI score and either itching or HRQoL exist but do not reach levels indicating very high correlation (ie, a correlation coefficient [0.9). 34 Itching may be an even stronger determinant of patient-perceived quality of life than PASI score is. 35 Therefore, the attributes evaluated here can be considered in the same conjoint analysis.…”
Section: Survey Approachmentioning
confidence: 99%